Ketogenic diets are beneficial for athletic performance: response to Burke and Whitfield - Noakes, T. D. (Medicine & Science in Sports & Exercise, 2024)
Systematic reviews of 17 (1) and 13 (2) studies conclude that "physical performance can be maintained when consuming a ketogenic diet (KD) compared with control (CON) (1)" and that "moderate-to-vigorous intensity exercise experiences no decrement (in performance) following adaptation to a KD" (2).